A STUDY OF ROLE OF EDUCATION IN REDUCING SOCIAL INEQUALITY - Raj Kishore (International Journal of Multidisciplinary Research and Studies, 2021)
Learners are better prepared to live sustainably and build continuous sustainable development practices in whichever line of work they choose if educational disparities are closed and they are given the opportunity to enhance their skills via education. As a result, enhancing the ability of people on a global scale, including communities and societies, to form well-informed opinions and support sustainable development. Within the context of the traditional educational system, which focuses on equipping students with the knowledge and skills they need to be successful in the working world, it integrates central tenets of education for sustainable development, such as the reduction of poverty, the protection of human rights, health and the environment, and climate change. Introduction By giving individuals more agency and making sure everyone is included, we can bring about a reduction in the inequality that exists in our society. In spite of the significant progress that has been made since the year 2000 in terms of lifting people out of poverty, inequalities and large disparities still exist in terms of income and wealth, as well as in terms of access to food, healthcare, education, land, clean water, and other resources that are necessary for people to live a life that is both full and dignified. Some society groups, such as those living in rural regions, women, young people, persons with disabilities, indigenous people, and others, have repeatedly concentrated near the bottom of distributions.